Designing high-performance amplifiers - Feucht, Dennis (Raleigh, NC SciTech Publishing, 2010)
This book covers the following topics: wideband amplification, precision amplification and high-performance amplification.
Electronic reproduction.
Keywords: Amplifiers (Electronics) -- Design and construction; Electronic circuit design; Electronic books